Understanding sales person turnover intention: relationship between job stress, workload and job satisfaction - Trisnawati, Asih; Wiwoho, Gunarso (Institute of Computer Science (IOCS), 2024)
Sales person becomes one of the assets and important factors in the company. What often happens in connection with the problem of sales person at the company is the employee's desire to leave his job (turnover intention) which ultimately requires the company to recruit employees. This research aims to find out the effect of job stress and workload on turnover intention mediated by job satisfaction. The data collection was carried out by disseminating questionnaires to 66 sales persons at PT Mitra Bisnis Keluarga Ventura Banyumas. The analytical tool used is SmartPLS 4 (Partial Least Squares) with structural equation modeling (SEM). The results of the study revealed the following: Job Stress (X1) has a negative and significant effect on Job Satisfaction (Z), Workload (X2) has a negative and significant effect on Job Satisfaction (Z), Job stress (X1) has a positive and significant effect on Turnover Intention (Y), Workload (X2) has a positive & significant effect on Turnover Intention (Y), Job Satisfaction (Z) has a negative and significant effect on Turnover Intention (Y), Job Stress (X1) has a positive & significant effect on Turnover Intention (Y) mediated by Job Satisfaction (Z) and Workload (X2) has a positive & significant effect on Turnover Intention (Y) mediated by Job Satisfaction (Z).